Compensation of oxygen doping in p-type organic field-effect transistors utilizing immobilized n-dopants - Barf, Marc‐Michael; Benneckendorf, Frank S.; Reiser, Patrick; Bäuerle, Rainer; Köntges, Wolfgang; Müller, Lars; Pfannmöller, Martin; Beck, Sebastian; Mankel, Eric; Freudenberg, Jan; Jänsch, Daniel; Tisserant, Jean-Nicolas; et al. (Advanced Materials Technologies, 2021)
Poly(3-hexyl-thiophene-2,5-diyl) (P3HT) is one of the most commonly used materials in organic electronics, yet it is considered to be rather unattractive for organic field-effect transistors (OFETs) due to its tendency to oxidize under aerobic conditions. Strong p-doping of P3HT by oxygen causes high off-currents in such devices opposing the desired high on/off-ratios. Herein, a new application-oriented method involving the recently developed immobilizable organic n-dopant 2-(2-((4-azidobenzyl)oxy)phenyl)-1,3-dimethyl-2,3-dihydro-1H-benzoimidazol (o-AzBnO-DMBI) is presented allowing to process and operate P3HT OFETs in air. The n-dopants compensate oxygen doping by trapping generated free holes, thereby rediminishing OFET off-currents by approximately two orders of magnitude. At the same time, field-effect mobilities remain high in the order of up to 0.19 cm2 V−1 s−1. Due to the covalent attachment of the dopants to the host matrix after photochemical activation, a drift of the otherwise mobile ions within the device is prevented even at high operating voltages and, thus, hysteresis in the corresponding transfer characteristics is kept low. In this manner, the air instability of P3HT OFETs is successfully resolved paving an auspicious way toward OFET mass production. As the immobilization process employed here is nonspecific with respect to the host material, this strategy is transferable to other p-type semiconductors.